TANGGUNG JAWAB RUMAH SAKIT TERHADAP TENAGA MEDIS DALAM KESELAMATAN DAN KESEHATAN KERJA AKIBAT PELAYANAN MEDIS - Maharja Jathi Perkasa (Fakultas Hukum Universitas Islam Malang, 2021)
he hospital is a health service that contained risks of occupational health and safety for The hospital is a health service that contained risks of occupational health and safety for its medical personnel, so the need for hospital occupational health and safety (K3RS) project to avoid those risks. An organization such as committee needed to ensure optimal K3RS management. This research formulation of the problem are the legal responsibility of the hospital to the medical personnel for K3 due to medical services in the hospital and the legal consequence of the absence of the K3RS Committee. This reasearch used normative juridical with statue approach and conseptual approach. The result showed that the hospital is responsible for problems in the scope of K3RS, responsibility related to the obligations set by the government and legal responsibility in carrying out the regulations. The result was, if the hospital did not formed an K3RS committee, they have to be legally responsible, for both criminal and civil law. Since hospital held responsibility to form a K3RS committee. According to the regulation from Hospital Accreditation Committee (KARS), director of the hospital held the responbility to fulfill this requirement.